The Hyperlinked Society: Questioning Connections in the Digital Age - Lokman Tsui; Joseph Turow (University of Michigan Press, 2008)
Links" are among the most basic—and most unexamined—features of online life. Bringing together a prominent array of thinkers from industry and the academy, The Hyperlinked Society addresses a provocative series of questions about the ways in which hyperlinks organize behavior online. How do media producers' considerations of links change the way they approach their work, and how do these considerations in turn affect the ways that audiences consume news and entertainment? What role do economic and political considerations play in information producers' creation of links? How do links shape the size and scope of the public sphere in the digital age? Are hyperlinks "bridging" mechanisms that encourage people to see beyond their personal beliefs to a broader and more diverse world? Or do they simply reinforce existing bonds by encouraging people to ignore social and political perspectives that conflict with their existing interests and beliefs? This pathbreaking collection of essays will be valuable to anyone interested in the now taken for granted connections that structure communication, commerce, and civic discourse in the world of digital media.